Improving Students Critical Thinking Skills Through Problem Solving Methods - Sudrajat Sudrajat; Ilaina Ilaina; Anggi Nayla Najihah; Cahayuna Kalonika Zahra; Yazid Bustomi (JIPSINDO, 2026)
This research was motivated by the low critical thinking skills and learning outcomes of  Social Studies subjects of SMP Negeri 1 Karau Kuala, Barito Selatan which are caused by the dominance of conventional learning methods. To address this problem, this study focuses on analyzing the effectiveness of implementing the problem-solving method as an effort to improve both competencies. This study uses the Classroom Action Research (CAR) design of the Kemmis and Taggart model, which was implemented in two cycles on 19 students. Data collection was carried out through essay tests to measure critical thinking skills and learning outcomes, as well as observations to monitor learning activities. The results of the study showed a significant progressive increase. The level of student learning completion increased from only 15.79% in the pre-cycle, to 42.11% in Cycle I. The turning point occurred in Cycle II, where replacing the media from less effective videos to more focused static images successfully increased the completion rate to 78.95% and individual critical thinking competencies reached 84.21%. It was concluded that the problem-solving method is proven to be effective, but its success is highly dependent on the selection of the right media. The synergy between active learning models and focused visual media is the main key to improving students' critical thinking skills.